2019
DOI: 10.5840/ajs20198754
|View full text |Cite
|
Sign up to set email alerts
|

The Verbal-Kinesic Enactment of Contrast in North American English

Abstract: In this paper, I explore the linguistic and kinesic expression of contrast—the pitting of one position, object, or idea, against another. The archetype utterance for the embodied expression of contrast in English is the bipartite construction On the one hand . . . . On the other hand . . . . in which hand gestures are often performed sequentially along the sagittal axis (first on one side and then on the other side of the body) to depict the two options. However, English speakers have a variety of other lingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Some of the preference statements included a second hedge within the preference statement, e.g., I don't know, but I guess I agree more with that, as opposed to hard to know, but his argument makes more sense to me. Although this may have introduced more variability, this was done to incorporate the most natural speech possible in an experimental context; corpus studies have shown that speakers very frequently "stack" highly stanced elements such as hedges (Hinnell, 2019(Hinnell, , 2020.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the preference statements included a second hedge within the preference statement, e.g., I don't know, but I guess I agree more with that, as opposed to hard to know, but his argument makes more sense to me. Although this may have introduced more variability, this was done to incorporate the most natural speech possible in an experimental context; corpus studies have shown that speakers very frequently "stack" highly stanced elements such as hedges (Hinnell, 2019(Hinnell, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, in this study the stimulus speaker gestured only with PUOH gestures. However, the corpus studies in Hinnell (2019Hinnell ( , 2020 suggest that speakers also regularly use other hand forms as well as other body articulators (e.g., head movements side to side) to indicate contrast, particularly when the referents are abstract. The question arises, then, whether other handshapes would affect the comprehension of contrastive gestures of preference and whether the effect is the same if the contrast is indicated in the head rather than the hands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the unbalanced interpersonal power dynamics found in certain settings (e.g., in contexts of instruction, see Goldin-Meadow, 2003 ; Hsu et al, to appear ) are to a large extent absent. Indeed, a growing number of studies on multimodal communication have examined television data for similar reasons [see the studies drawing on the databases of the Red Hen Lab ( www.redhenlab.org ) and the TV News Archive ( archive.org/details/tv ); e.g., Steen and Turner, 2013 ; Winter et al, 2013 ; Zima, 2017 ; Hinnell, 2018 , 2019 ]. On top of all these, TV talk shows abound in recounts of past experiences and enactments of hypothetical scenarios, both of which contribute to the richness of depicting.…”
Section: Methodsmentioning
confidence: 99%